PENGARUH TERAPI WARNA HIJAU TERHADAP TEKANAN DARAH SISTOLIK PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA WANA SERAYA DENPASAR - Ni Made Budi Arthini (Coping: Community of Publishing in Nursing, 2015)
Increased of Systolic Blood Pressure (SBP) is a manifestation of cardiovascular organ degeneration in elderly. One of non pharmacological therapies that can affect blood pressure is green color therapy. Green is able to reduce tension, suppresses the activity of the sympathetic nervous system, dilates capillaries, and stimulates the pituitary to release neurohormones, which can lower blood pressure. This study aims to determine the therapeutic effect of green color on SBP in elderly in the Elderly Social Institution of Wana Seraya Denpasar. This research is a quasy-experimental study (pre-test and post-test with control group design). Samples consisted of 30 elderly people that selected by purposive sampling, divided into control and experimental groups. The experimental group was given green color therapy for 10 minutes every day for seven days. SBP pre-test and post-test in both groups was measured by sphygmomanometer and stethoscope. The results show an increase of 0,0573 mmHg at an average SBP in control group, and decrease of 6,54 mmHg on average SBP in experimental group. Based on the independent sample t-test, this difference was statistically significant, with t value of -10,456 and Sig. (2-tailed) of 0,000, which means there is a therapeutic effect of green color therapy for systolic blood pressure in elderly in the Elderly Social Institution of Wana Seraya Denpasar